Design of Control Method for Improving Current Quality of Wind Power Grid-Connected Inverter. Issue 1 (March 2021) - Li, Y; Zhang, Z Y; Wang, P G; Zhuang, Y; Liu, S
Abstract: The problem of suppression of nonlinear random impulse disturbance in grid-connected wind power generation is studied in this paper. The mathematical model of grid side converter of wind power system is obtained by using Kirchhoff law. A feedback synchronization controller is designed to suppress the disturbance of current. With the help of Lyapunov stability theory, the effectiveness of the synchronization controller is verified. Further effectively restrain the nonlinear random disturbance caused by the current connected to the grid, so that the current generated by the wind turbine is synchronized with the current generated by the power grid. Finally, the simulation verification is carried out. The simulation results show that the effectiveness of the proposed control method.